Modern India and Dietary Calcium Deficiency—Half a Century Nutrition Data—Retrospect–Introspect and the Road Ahead - Harinarayan, Chittari Venkata; Akhila, Harinarayan; Shanthisree, Edara (Frontiers in Endocrinology, 2021)
Calcium and vitamin D are inseparable nutrients required for bone health. In the past half a century, the dietary calcium intake of rural, tribal, and urban India has declined. The high intake of cereals and low intake of milk and milk products is seen across rural and tribal subjects, despite India being the largest milk and cereal producer in the world. The intake of cereals, milk & milk products were similar in both urban and metropolitan subjects. Over the past half a century, the average 30day consumption of cereals in the rural and urban population has declined by 30%. The Private Final Consumption Expenditure(PFCE) has declined by 40% for food items and increased by 40% for non-food items. The Per Capita Cereal Consumption(PCCC)has declined despite sustained raise in Monthly Per capita Consumption Expenditure(MPCE)in both rural and urban households. The cereal consumption was the highest in the lowest income group, despite spending smaller portion of their income, as cereals were supplied through public distribution system(PDS). About 85% of the Indian population are vitamin D deficient despite abundant sunlight. Dietary calcium deficiency can cause secondary vitamin D deficiency. There is a decline in dietary calcium in the background of upward revision of RDI/RDA. There is a gap in the production-consumption-supply chain with respect to dietary calcium. To achieve a strong bone health across India, it is imperative to revisit the guidelines for calcium along with population based strategies addressing different segments including supplementing dietary/supplemental calcium in ICDS, mid-day-meals scheme, public distribution system, educational strategies. Other measures like mass food fortification, biofortification, leveraging digital technologies, investments from corporate sector are some measures which can address this problem. India is a vast country with diverse social, cultural and dietary habits. No single measure can address this problem and requires a multi-pronged strategic approach to tackle the dietary calcium deficiency. India should focus on multi-pronged strategy to tackle the problem of strong bone health while solving the problem of nutritional deficiency.